The Effectiveness of Song-Based Instruction in Enhancing EFL Students’ Vocabulary Mastery: Vocabulary - Nurul Mawaddah U Makuta; Konder Manurung; Afrillia Anggreni; Sriati Usman (MASI Mandiri Edukasi, 2026)
Vocabulary mastery is a fundamental component of language learning, and innovative instructional strategies are needed to improve students’ vocabulary outcomes. This study aimed to investigate the effect of the Song media on the vocabulary development of tenth-grade students at SMA Negeri 5 Palu in the 2025/2026 academic year. The research employed a quantitative approach with a quasi-experimental design using a pre-test and post-test control group. Two classes were selected by random sampling and assigned to the experimental and control groups. Students’ vocabulary achievement data were collected through vocabulary tests and analyzed statistically using SPSS, with the Mann-Whitney U Test applied to examine differences between groups. The statistical analysis revealed a significant difference in vocabulary learning outcomes between the two groups. This was indicated by an Asymp. Sig. (2-tailed) value of < 0.001, which was lower than the 0.05 significance level. In addition, the experimental group achieved a higher mean rank (36.96) than the control group (20.04), showing better post-test performance after the treatment. These findings imply that integrating songs into vocabulary instruction is significantly more effective than conventional teaching methods for improving students’ vocabulary learning outcomes.